Content Analysis of Czech School Biology Textbook with Regard to Human Evolution Topics - Dvořáková, Radka Marta; Absolonová, Karolína (Scientia in educatione, 2017)
This article is about factual accuracy of the issue of human evolution as presented in eighteen Czech biology textbooks. We focused upon three key fields — the conception of H. sapiens among living beings, the conception of human evolution and analyse of species. We point out the rank of outdated information and mistakes in the biology textbooks which can complicate the understanding of this issue like linear image of evolution, presenting H. sapiens as a goal of evolution and / or the most perfect animal or labelling H. sapiens sapiens as another taxon in addition to H. sapiens.